Multi-omics analysis of the biological mechanism of the pathogenesis of non-alcoholic fatty liver disease - Lin, Jie; Zhang, Ruyi; Liu, Huaie; Zhu, Yunzhen; Dong, Ningling; Qu, Qiu; Bi, Hongyan; Zhang, Lihua; Luo, Ou; Sun, Lei; Ma, Mengjuan; You, Jing (Frontiers in Microbiology, 2024)
Background: Non-alcoholic fatty liver disease (NAFLD) is a type of liver metabolic syndrome.Employing multi-omics analyses encompassing the microbiome, metabolome and transcriptome is crucial for comprehensively eclucidating the biological processes underlying NAFLD.Methods: Hepatic tissue, blood and faecal samples were obtained from 9 NAFLD model mice and 8 normal control mice. Total faecal microbiota DNA was extracted, and 16S rRNA was amplified, to analyse alterations in the gut microbiota (GM) induced by NAFLD. Subsequently, diagnostic strains for NAFLD were screened , and their functional aspects were examined. Differential metabolites and differentially expressed genes were also screened, followed by enrichment analysis . Correlations between the differential microbiota and metabolites, as well as between the DEGs and differential metabolites were studied. A collinear network involving key genes-,microbiota-and metabolites was constructed.